Influence of SiC fiber on thermal cycling lifetime of SiC fibers /YSZ thermal barrier coatings by atmospheric plasma spraying. Issue 15 (15th October 2018) - Fang, Yongchao; Cui, Xiufang; Jin, Guo; Lu, Bingwen; Wang, Fuyuan; Liu, Ming; Wen, Xin
Abstract: The initiation and propagation of cracks under thermal stresses easily is one of the problems limiting the thermal cycling lifetime of thermal barrier coatings (TBCs). In order to improve the thermal cycling lifetime, SiC fibers were introduced to yttria stabilized zirconia (YSZ) coating deposited on In738LC substrate by atmospheric plasma spray (APS). Phase composition, thermal cycling behaviors and fiber toughening mechanisms of coatings were systematically investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and thermal cycling test. Results showed that the thermal cycling lifetime and fracture toughness of SiC fibers/YSZ coatings could reach 442 ± 13 and 1.54 ± 0.19 MPa m respectively, which were 1.6 times and 1.3 times higher than that of conventional TBCs. There are two stages of fiber reinforced during thermal cycling, and the first is crack deflection and termination, the second is fiber debonding, pull-out, breakage and bridging. Meanwhile, SiC fibers could prevent the stress-activated ZrO2 martensitic transformation by reducing the stress in the lattice.